Tinjauan Naratif: Isu Gender Pada Perilaku Bullying di Kalangan Remaja - Aini, Kurrota (Yayasan Arrahman Nahdlatul Wathan, 2023)
Bullying behaviors is still a recent phenomenon among teenagers and often occurs in schools. Bullying cases that have gone viral on social media in recent years are very worrying, where both adolescents boys and adolescents girls gang up to bully their friends. Some cases have recorded victims of bullying ending in suicide. The purpose of this study is to collect and analyze evidence through Literature Review on whether there are gender issues in bullying behavior among adolescents. The research method used in this research is qualitative through a narrative literature review approach. The results of the study found that male adolescents are more dominant in being the subject (perpetrator) of bullying than female adolescents. However, it does not rule out the possibility of adolescents girls acting aggressively as bullying perpetrators against their friends like adolescents boys. On the other hand, adolescent girls and adolescent boys both have the opportunity to be victims of bullying committed by others, especially their friends. Therefore, parents and schools must pay attention to bullying behaviors at school for both male and female adolescents.